Li-ion storage in an amorphous, solid, spheroidal carbon anode produced by dry-autoclaving of coffee oil. (July 2018) - Kim, Kyungho; Adams, Ryan A.; Kim, Patrick J.; Arora, Anjela; Martinez, Enrico; Youngblood, Jeffrey P.; Pol, Vilas G.
Abstract: A facile, one-step, solvent-free 'dry autoclaving' synthesis method utilized coffee oil as carbon precursor to obtain micrometer diameter spheroidal carbon particles for lithium ion battery anodes. The spheroidal morphology resulted from the evaporation of liquid oil into liquid/gas phase interphase at elevated temperature (700 °C), followed by solid/gas sublimation interactions during cooling (below 350 °C) in a closed autoclave. A mechanism of spheroidal carbon formation is proposed considering the precursor's composition and chemical interactions during autoclaving. The solid spheroidal carbon exhibits 0.85 g cc −1 tap density and 5 m 2  g −1 surface area. Galvanostatic cycling performed at 100 mA g −1 current density delivered a capacity of 290 mAh g −1 after 200 cycles. Battery testing at elevated temperature (50 °C) increased the capacity (350 mAh g −1 after 200 cycles at 100 mA g −1 ), but with decreased Coulombic efficiency due to faster electrolyte depletion by augmented reaction kinetics. The spherical morphology and carbon structuring are maintained after 250 charge-discharge cycles, indicating the long term stability of the spheroidal carbon as Li-ion anode material. Graphical abstract: Image 1